SUBSIDY REINVESTMENT AND EMPOWERMENT PROGRAMME (SURE-P) AND YOUTH DEVELOPMENT IN IMO EAST SENATORIAL ZONE, IMO STATE - Obilor, Ngozi Mary; Osita-Njoku, Agnes (African Journal of Social and Behavioural Sciences, 2021)
Subsidy Reinvestment and Empowerment Programme (SURE-P) was aimed at ensuring youth development through youth empowerment programmes that were aimed at creating jobs and alleviating poverty. However, SURE-P may not have been able to actualize this mandate in the 36 states of the federation. Thus, this study sought to examine the extent to which SURE-P was able to achieve its mandate in Imo East senatorial zone. The study reviewed Literature that were related to SURE-P and adopted Abraham Maslow’s theory of hierarchy of needs as its theoretical framework. This theory was used to explain the extent to which SURE-P was able to ensure youth development in Imo east senatorial zone however, data were collected using primary sources of data collection like, Key Persons Interview (KPI), non-participant observation and secondary sources of data collection technique like internet materials. The interviewees were chosen from Nguru, Uwo, Umuneke Umugwuma and Iho in Aboh-Mbaise, Mbaitoli, Ngor Okpala, Owerri West and Ikeduru through a purposive sapling technique. Findings revealed that SURE-P was able to provide employment opportunities for youths but youths were underpaid. It was also found out that the implementation of SURE-P suffered some bias and that the Imo east senatorial zone did not benefit from the Technical Vocational Education and Training (TVET) programme of SURE-P. The study recommends that beneficiaries of subsequent interventionist programmes be paid higher amount of stipends without any form of inconsistency and that skill acquisition and permanent employment opportunities should be considered as critical issues in ensuring youth development in the zone.